Pembatalan Akad Wakalah Oleh Kurir Dalam Prespetif Fikih Muamalah - Lailatul Rohmah; Mustofa, Imron (Al-Urban: Jurnal Ekonomi Syariah dan Filantropi Islam, 2023)
Fast and practical online transactions have become the top choice for consumers. However, in online transactions carried out through wakalah or representative contracts, there is a phenomenon of unilateral cancellation by couriers which often causes problems for sellers and buyers. Such cancellations, sometimes carried out for no apparent reason, result in loss of time, cost and effort for the seller, as well as the inability of the buyer to obtain the desired item. This study aims to determine the cancellation of the wakalah contract by representatives in muamalah jurisprudence, and provide solutions to these problems. The method used in the analysis of this problem is qualitative using a descriptive approach. Unilateral cancellation by courier is permissible as according to the Hanafi school that a representative is allowed to decide for himself without the knowledge of the representative. However, such a cancellation should not be made without careful consideration, on the other hand, the courier as a representative in the wakalah contract has responsibility for his duties, which should be carried out with full trust